Severe malaria is associated with a deficiency of von Willebrand factor cleaving protease, ADAMTS13 - Löwenberg, Ester C.; Charunwatthana, Prakaykaew; Cohen, Sophie; Born, Bert-Jan van den; Meijers, Joost C. M.; Yunus, Emran B.; Hassan, Mahtab B.; Hoque, Gofranul; Maude, Richard J.; Nuchsongsin, Forradee; Levi, Marcel; Dondorp, Arjen M. (Thrombosis and Haemostasis, 2010)
Severe falciparum malaria remains a major killer in tropical countries. Central in the pathophysiology is mechanical obstruction in the micro-circulation caused by cytoadherence and sequestration of parasitized erythrocytes. However, the pathogenesis of many features complicating severe malaria, including coma, renal failure and thrombocytopenia, remains incompletely understood. These disease manifestations are also key features of thrombotic thrombocytopenic purpura, a life-threatening disease strongly associated with a deficiency of the von Willebrand factor (VWF) cleaving protease, ADAMTS13. We measured plasma ADAMTS13 activity, VWF antigen and VWF propeptide levels in 30 patients with severe falciparum malaria, 12 patients with uncomplicated falciparum malaria and 14 healthy Bangladeshi controls. In patients with severe malaria ADAMTS13 activity levels were markedly decreased in comparison to normal controls (mean [95%CI]: 23% [20–26] vs. 64% [55–72]) and VWF antigen and propeptide concentrations were significantly elevated (VWF antigen: 439% [396–481] vs. 64% [46–83]; VWF propeptide: 576% [481–671] vs. 69% [59–78]). In uncomplicated malaria VWF levels were also increased compared to healthy controls but ADAMTS13 activity was normal. The results suggest that decreased ADAMTS13 activity in combination with increased VWF concentrations may contribute to the complications in severe malaria.
Keywords: ADAMTS13; falciparum malaria; thrombotic microangiopathy; thrombotic thrombocytopenic purpura; von Willebrand factor cleaving pro-tease